Photon balance in the fiber laser model - Barmenkov Yuri; Minguela-Gallardo Josué A.; Muniz-Cánovas Pablo; Aboites Vicente (Open Physics)
In this article, we present the results of the numerical study related to the balance of photons in a fiber laser simulated by the traveling wave model (TWM). This study is essential since the balance of photons is closely related to the fundamental physical law of conservation of energy. For generality, we consider that active ions of the gain fiber present excited state absorption at both the laser and pump wavelengths and the fiber background loss. We compare the results of simulation based on the TWM, in which the radial distributions of the populations of the energy levels of the active ions are accounted for, with those obtained when these distributions are omitted. We show that, in the first case, the balance of photons is wholly preserved, while in the second case, the balance of photons is disturbed by tens of percent. The physics behind this result is discussed.